APAKAH BEBAN KERJA MENTAL BERHUBUNGAN DENGAN TINGKAT KECEMASAN PADA KARYAWAN BANDARA? - Muhammad Fajri Raihan; Magdalena Wartono (Jurnal Akta Trimedika, 2025)
Anxiety was the anticipation of future danger accompanied by feelings of dysphoria and somatic symptoms. Anxiety often occured in employees within the early adults (ages 26-35). Risk factors of anxiety in employees included genetics, social and family environmental factors, and mental workload. The impact of mental workload on employees could affect mental health, specifically the level of anxiety, that could implicate the job performance. The aim of this study was to assess the relationship between gender, age, and mental workload with the anxiety levels of airport employees. The design of the study was observational analytic cross-sectional approach. A sample size of 125 subjects were obtained through cluster random sampling. Primary data was collected using the HARS and NASA-TLX questionnaires. Data were analyzed with SPSS using the Kolmogorov-Smirnov and Kendall's Tau tests. There were 69 male employees and 53 individuals were in the early adulthood (26-35 years). For mental workload, 51 employees had a slightly high workload and 47 employees had severe anxiety.The bivariate analysis indicated that there was no relationship between gender and anxiety levels (p=0.709) as well as age and anxiety levels (p=0.142). However, there was a relationship between mental workload and anxiety levels (p=0.005). Mental workload is related with anxiety levels in airport workers.